CHILD EXPLOITATION AS A HUMAN RIGHTS VIOLATION: A JURIDICAL ANALYSIS IN THE CONTEXT OF NATIONAL AND INTERNATIONAL LAW IN INDONESIA - Irma Romi Anto (Yayasan Pendidikan Islam Almatani, 2025)
Child exploitation constitutes a grave violation of human rights, directly undermining the dignity, development, and future of children as the nation's next generation. This article presents a juridical analysis of how Indonesian national law and international legal instruments protect children from various forms of exploitation, including economic exploitation, sexual exploitation, and trafficking. Employing a normative legal approach, this study examines relevant Indonesian legislation-such as the Child Protection Act and provisions in the Criminal Code-alongside international frameworks, notably the United Nations Convention on the Rights of the Child (CRC). The findings indicate that despite Indonesia’s ratification of key international treaties and the existence of comprehensive domestic legal norms, significant challenges persist in enforcement, institutional coordination, and victim recovery processes. This paper argues for a more integrated and rights-based legal framework, improved law enforcement capacity, and stronger institutional mechanisms to ensure effective child protection. Strengthening these aspects is essential to align national practices with universally recognized human rights standards and to combat child exploitation more effectively